Evaluation of the efficacy and safety of terguride in patients with fibromyalgia syndrome: results of a twelve-week, multicenter, randomized, double-blind, placebo-controlled, parallel-group study - Distler, Oliver; Eich, Wolfgang; Dokoupilova, Eva; Dvorak, Zdenek; Fleck, Martin; Gaubitz, Markus; Hechler, Manfred; Jansen, Jan-Peter; Krause, Andreas; Bendszus, Martin; Pache, Lothar; Reiter, Rudolf; et al. (Arthritis & rheumatism, 2010)
Objective: To assess the efficacy and safety of terguride, a partial dopamine agonist, in patients with fibromyalgia syndrome (FMS). Methods: In a 12-week, multicenter, double-blind, placebo-controlled, parallel-group study, 99 patients were randomized at a ratio of 2 to 1 to receive terguride or placebo. Over 21 days, the dosage was titrated to a maximum daily dose of 3 mg of terguride or placebo, and this fixed dosage was continued over 9 weeks. The primary efficacy variable was the intensity of pain (100-mm visual analog scale). Secondary efficacy variables included the Fibromyalgia Impact Questionnaire (FIQ) score, the tender point score (TPS), and the Hamilton Depression Scale (HDS) score. During the study, patients were evaluated for the presence of cervical spine stenosis by magnetic resonance imaging (MRI). Results: No significant differences in the change in pain intensity, FIQ score, TPS, or HDS score between baseline and 12 weeks were observed in the terguride group as compared with the placebo group. Cervical spine stenosis was detected in 22% of the patients. Only patients with cervical spine stenosis responded to terguride treatment. FIQ scores improved significantly (per-protocol analysis), and pain intensity, the TPS score, and the HDS score showed a trend toward improvement in the terguride group as compared with the placebo group. Terguride treatment was safe. Only those adverse events already known to be side effects of terguride were observed. Premature termination of the study in patients receiving terguride (26%) occurred predominantly during up-titration and in the absence of comedication for treatment of nausea. Conclusion: Terguride treatment did not improve pain, the FIQ score, the TPS, or the HDS score in the total study population. However, a subgroup of patients with cervical spine stenosis seemed to benefit from terguride treatment.